Optimising Emotions, Incubating Falsehoods How to Protect the Global Civic Body from Disinformation and Misinformation - Bakir, Vian.; McStay, Andrew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book deconstructs the core features of online misinformation and disinformation. It finds that the optimisation of emotions for commercial and political gain is a primary cause of false information online. The chapters distil societal harms, evaluate solutions, and consider what must be done to strengthen societies as new biometric forms of emotion profiling emerge. Based on a rich, empirical, and interdisciplinary literature that examines multiple countries, the book will be of interest to scholars and students of Communications, Journalism, Politics, Sociology, Science and Technology Studies, and Information Science, as well as global and local policymakers and ordinary citizens interested in how to prevent the spread of false information worldwide, both now and in the future. Vian Bakir is Professor in Journalism and Political Communication at Bangor University, UK. Her most recent book is Intelligence Elites & Public Accountability: Relationships of Influence with Civil Society (2019). Andrew McStay is Professor of Digital Life at Bangor University, UK. His most recent book is Emotional AI: The Rise of Empathic Media (2018). .
Part I Conceptual Tools and Contexts .-1 Optimising Emotion: Introducing the Civic Body -- 2 Core Incubators of False Information Online -- 3 Affective Contexts Worldwide -- 4 The Nature and Circulation of False Information -- 5 Feeling-Into the Civic Body: Affect, Emotions and Moods -- 6 Profiling, Targeting and the Increasing Optimisation of Emotional Life -- Part II Strengthening the Civic Body .-7 Harms to the Civic Body from False Information Online -- 8 Defending the Civic Body from False Information Online -- 9 Strengthening the Civic Body as the Bandwidth for Optimised Emotion Expands.
Keywords: Communication in politics; Journalism; Digital media; Political science; Mass media; Artificial intelligence; Political Communication; Journalism; Digital and New Media; Political Science; Media Sociology; Artificial Intelligence